2021
DOI: 10.1371/journal.pone.0253763
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and limitations: A comparative analysis of citizen science and expert recordings for bioacoustic research

Abstract: Citizen science is an approach that has become increasingly popular in recent years. Despite this growing popularity, there still is widespread scepticism in the academic world about the validity and quality of data from citizen science projects. And although there might be great potential, citizen science is a rarely used approach in the field of bioacoustics. To better understand the possibilities, but also the limitations, we here evaluated data generated in a citizen science project on nightingale song as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…It is important to understand the limitations of citizen science and ensure any assumptions are met before employing this method (e.g. Bauder et al, 2021;Jäckel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the limitations of citizen science and ensure any assumptions are met before employing this method (e.g. Bauder et al, 2021;Jäckel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Our opportunistic approach indeed led to a large collection of geo-referenced nightingale song recordings. We previously showed that the majority of our CS data were valid enough (Jäckel et al 2021 ) and of high value for dialect studies (Jäckel et al 2022 ). The development of the project over three nightingale breeding seasons has not yet been studied.…”
Section: Introductionmentioning
confidence: 67%
“…Using diverse dissemination activities such as events both inside and outside the MfN, midnight excursions and press coverage, the public was invited to download the 'Naturblick' app on their smartphones and record nightingale songs (for details see Jäckel et al 2021 ). Public events were free of charge, included two to 180 participants and by large took place in Berlin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling up ecoacoustics research will require a considerable effort to address the lack of standardization for acoustic data and metadata collection (Roch et al, 2016;Gibb et al, 2019), as well as the development of communities and platforms that enable the sharing of annotated datasets and tested species detection techniques. Enabling acoustic data categorization by citizen scientists also holds great promise (Jäckel et al, 2021). For example, citizen scientists engaging with Hoot Detective [a collaboration between the Australian Acoustic Observatory (A2O), the Australian Broadcasting Commission, Queensland University of Technology, and the University of New England, for National Science Week] have at the time of writing identified 2,624 native owl calls (Noonan, 2021).…”
Section: Introductionmentioning
confidence: 99%